Inequality-adjusted gender wage differentials in Germany - Ekaterina Selezneva; Philippe Van Kerm (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This paper exploits data from the German Socio-Economic Panel (SOEP) to re-examine the gender wage gap in Germany on the basis of inequality-adjusted measures of wage differentials which fully account for gender differences in pay distributions. The inequality-adjusted gender pay gap measures are significantly larger than suggested by standard indicators, especially in East Germany. Women appear penalized twice, with both lower mean wages and greater wage inequality. A hypothetical risky investment question collected in 2004 in the SOEP is used to estimate individual risk aversion parameters and benchmark the ranges of inequality-adjusted wage differentials measures.
Keywords: D63; J31; J70; 330; gender gap; wage differentials; wage inequality; expected utility; risk aversion; East and West Germany; SOEP; Singh-Maddala distribution; copula-based selection model